2018
DOI: 10.1161/circresaha.117.311950
|View full text |Cite|
|
Sign up to set email alerts
|

Yes-Associated Protein Promotes Angiogenesis via Signal Transducer and Activator of Transcription 3 in Endothelial Cells

Abstract: YAP binding sustained STAT3 in the nucleus to enhance the latter's transcriptional activity and promote angiogenesis via regulation of angiopoietin-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 65 publications
6
97
0
Order By: Relevance
“…YAP nuclear localization was impaired in the angiogenic front of Lpa4;Lpa6 iΔEC retinas. Several independent studies have revealed that endothelial YAP/TAZ mediate sprouting angiogenesis (31)(32)(33)(34)(35)(36). In this context, we propose LPA4 and LPA6 as regulators of sprouting angiogenesis that repress DLL4 expression by activating YAP/TAZ in ECs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…YAP nuclear localization was impaired in the angiogenic front of Lpa4;Lpa6 iΔEC retinas. Several independent studies have revealed that endothelial YAP/TAZ mediate sprouting angiogenesis (31)(32)(33)(34)(35)(36). In this context, we propose LPA4 and LPA6 as regulators of sprouting angiogenesis that repress DLL4 expression by activating YAP/TAZ in ECs.…”
Section: Discussionmentioning
confidence: 64%
“…A previous report showed that LPA-induced Gα12/Gα13 signaling activated YAP in HEK293 cells (30). Recently, several independent studies revealed that endothelial YAP/TAZ mediate sprouting angiogenesis (31)(32)(33)(34)(35)(36). However, the biological significance of GPCR-induced YAP/TAZ activation is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the reduction in H3K27ac marks on NOS3 enhancers may alter its response in PAH. Third, YAP1 promotes angiogenesis in endothelial cells 28 but YAP1 is not known to be regulated by TGFβ in endothelial cells 29 . Here too the impaired upregulation of YAP1 as well as NOS3 in response to TGFβ in PAH PAEC might underlie the impaired angiogenesis in these cells.…”
Section: Extensive Remodeling Of H3k27ac In Pah Patients Vs Controlsmentioning
confidence: 99%
“…In addition, phosphorylation of YAP at Y 357 increases its stability and in turn upregulates its activity (9). Recently, YAP was identified to be crucial in ECs in different biological processes, including angiogenesis (10) and atherosclerosis (11,12). Moreover, the suppression of YAP in response to LSS plays an important role in maintaining vessel homeostasis in ECs (11,12).…”
Section: Introductionmentioning
confidence: 99%